Instalasi Jaringan Internet dan Panel Surya Untuk Pengontrolan Absensi Siswa dan Keamanan CCTV di Masjid - Dzikri, Afdhol; Kurniawan, Dwi Ely; Resda, Dodi Prima (Politeknik Negeri Batam, 2023)
Nowadays, the application of technology in mosques is important to help the smooth running of activities. Miftachul Jannah Mosque, Duriangkang Village, Sungai Beduk Subdistrict, Batam City seeks to overcome two main problems; first, the repeated theft of charity box money. Second, there are frequent power outages that disrupt the recitation process. As a solution, the service team conducted research aimed at improving security and electricity availability through the installation of internet networks and solar panels, which are integrated with CCTV systems. The object of this research focuses on the application of technology in the mosque environment to ensure the continuity of religious activities without obstacles. The Participatory Rural Appraisal (PRA) method was applied to design and implement the system with the participation of mosque administrators and teachers. The results show that the utilization of solar power generation significantly supports the operation of electronic equipment, such as street lighting and power sources for wifi routers and CCTV. The implementation of this system has proven to provide tangible benefits, in the form of a reliable source of renewable energy and increased security functions through internet-connected CCTV, which also supports the teaching and learning process with an online attendance system for TPQ students. And the administrators and teachers are satisfied with this service.